Foreign Ownership and Exchange Rates on Transfer Pricing Decisions in Manufacturing Companies Listed on The Indonesia Stock Exchange - Fathinus Syafrizal; Ahmad Farabi (Economics, Business, Accounting & Society Review, 2023)
Transfer pricing is the company's policy in determining the transfer price of a transaction. Improved cash flow performance and marketing objectives encourage companies to allocate overhead costs and design strategies in estimating the transfer prices of goods and services produced. This study explores foreign ownership and exchange rates' impact on transfer pricing. This study uses a quantitative approach by examining foreign ownership and exchange rate variables against transfer prices. The data used are the audited financial statements of manufacturing companies listed on the Indonesia Stock Exchange for 2017-2021. The results of this study show that foreign ownership and foreign exchange rates have no impact on transfer prices. This research contributes to the transfer pricing literature regarding transfer pricing policies relating to foreign investment risk and the political power of those who support local government objectives.